PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAMS ACHIEVEMENT DIVISION) MELALUI METODE TEAM TEACHING PADA MATERI SEGIEMPAT UNTUK MELATIH KECAKAPAN HIDUP SISWA - Lisanul Uswah Sadieda; Nurul Avivah (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2011)
The graduates of all education level are expected to have all aspect in accordance with national education goals, one of which is life skill. Life skill development in school is influenced by learning process in the classroom, including selection of appropriate learning model. Theoretically, cooperative model STAD (Student Teams Achievement Division) type through team teaching method is suitable to train students’ life skill. Because of that, the aim of this research is to know the students’ life skill during the learning process of quadrilateral topic using this STAD learning model in the seventh grade of SMP Negeri 4 Surabaya. The research result show that students’ life skill are good. It is shown from the average score of rational thinking skill at 2,83 and social skill at 2,63.